Efficiency and importance of dairy enterprises - Penchuk, Anna; Cherednichenko, Galina (НУХТ, 2011)
In the article the authers disclosed the tasks of and importance of work of dairy enterprises in Ukraine .
Keywords: ефективність; эффективность; efficiency; кафедра ділової іноземної мови та міжнародної комунікації